1994
DOI: 10.1111/j.1399-3054.1994.tb02192.x
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid controls dormancy development and bulb formation in lily plantlets regenerated in vitro

Abstract: Plantlets of lily regenerated in vitro from scale explants consist of scales and leaves from which the base of the petiole has swollen to a scale. Fluridone, an inhibitor of ABA‐synthesis, applied during culture in vitro, inhibited the swelling of the petioles and promoted leaf formation. At high fluridone concentrations (10 or 33μM), swelling was completely blocked, and plantlets consisted of leaves only. Addition of ABA during the regeneration in vitro had the opposite effect and resulted in plantlets with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 24 publications
(13 reference statements)
0
21
0
Order By: Relevance
“…There are reports demonstrating the role of ABA in bulb formation in Lilium (Klerk 1992, Kim et al 1994. Also, role of P 333 in enhancing bulblet formation has earlier been reported (Klerk 1992, Thakur et al 2002.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 90%
“…There are reports demonstrating the role of ABA in bulb formation in Lilium (Klerk 1992, Kim et al 1994. Also, role of P 333 in enhancing bulblet formation has earlier been reported (Klerk 1992, Thakur et al 2002.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 90%
“…Endodormancy, a part of dormancy, refers to a state of buds regulated by internal factors where growth is possible only after plants have been exposed to sufficient amount of chilling (Lang et al 1987;Welling and Palva 2006). Dormancy of in vitro plants has been frequently studied on bulb plant species (Maksimović et al 2008;Kwang-Soo Kim et al 1994;Aguettaz et al 1990;Delvallée et al 1990). Some investigations of partial aspects related to endodormancy were made on fruit trees in vitro but there is a lack of studies for the investigation of dormancy induction and release in trees in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of hyacinth bulblet formation in vitro and their growth was inhibited by ABA (Pierik and Steegmans 1975). Kim et al (1994) demonstrated that in lily cultured in vitro an inhibition of ABA synthesis by fluridone gave plantlets consisting solely of leaves while the presence of ABA induced bulb formation with scales only. Work is now in progress in order to precise the hormonal regulation of the regeneration pattern in fritillary.…”
Section: Discussionmentioning
confidence: 99%